Endothelial chimerism in chronic sclerotic‐type chronic graft‐versus‐host disease (GVHD) and GVHD‐associated angiomatosis. (10th June 2016) - Kaffenberger, B.H.; Zhang, E.; Duncan, J.R.; Jaglowski, S.; Klisovic, R.B.; Devine, S.M.; Wong, H.K.; Gru, A.A.
Summary: Graft‐versus‐host disease‐associated angiomatosis (GVHD‐AA) is an uncommon manifestation of chronic GVHD consisting of friable vascular proliferations. Using fluorescence in situ hybridization, we demonstrate the presence of donor‐derived endothelial cells within areas of GVHD‐AA. This is the first documented occurrence of a benign neoplastic growth in relationship to a form of chronic GVHD. Abstract : What's already known about this topic? Graft‐versus‐host disease‐associated angiomatosis (GVHD‐AA) is a recently described uncommon presentation of endothelial proliferation developing exclusively within areas of sclerotic‐type GVHD, resulting in friable capillary proliferations. Transplanted human bone marrow has recently been shown to contribute to normal vascular endothelium in female patients with sex‐mismatched donors. What does this study add? Based on two female patients with sex‐mismatched donors, using fluorescence in situ hybridization we show that donor endothelial cells are present in GVHD‐AA. While endothelial chimerism has been previously documented following transplantation, this report documents for the first time the occurrence of a benign neoplastic growth in relationship to a form of chronic GVHD.